Adenosine kinase inhibition enhances microvascular dilator function and improves left ventricle diastolic dysfunction. (25th May 2020) - Davila, Alec; Tian, Yanna; Czikora, Istvan; S. Weissman, Amanda; Weinand, Nicholas; Dong, Guangkuo; Xu, Jiean; Li, Jie; Su, Huabo; Kapuku, Gaston; Huo, Yuqing; Bagi, Zsolt
Abstract: Objective: Inhibition of adenosine kinase (ADK), via augmenting endogenous adenosine levels exerts cardiovascular protection. We tested the hypothesis that ADK inhibition improves microvascular dilator and left ventricle (LV) contractile function under metabolic or hemodynamic stress. Methods and Results: In Obese diabetic Zucker fatty/spontaneously hypertensive heart failure F1 hybrid rats, treatment with the selective ADK inhibitor, ABT‐702 (1.5 mg/kg, intraperitoneal injections for 8‐week) restored acetylcholine‐, sodium nitroprusside‐, and adenosine‐induced dilations in isolated coronary arterioles, an effect that was accompanied by normalized end‐diastolic pressure (in mm Hg, Lean: 3.4 ± 0.6, Obese: 17.6 ± 4.2, Obese + ABT: 6.6 ± 1.4) and LV relaxation constant, Tau (in ms, Lean: 6.9 ± 1.5, Obese: 13.9 ± 1.7, Obese + ABT: 6.0 ± 1.1). Mice with vascular endothelium selective ADK deletion (ADK VEC KO) exhibited an enhanced dilation to acetylcholine in isolated gracilis muscle (lgEC50 WT: −8.2 ± 0.1, ADK VEC KO: −8.8 ± 0.1, P  < .05) and mesenteric arterioles (lgEC50 WT: −7.4 ± 0.2, ADK VEC KO: −8.1 ± 1.2, P  < .05) when compared to wild‐type (WT) mice, whereas relaxation of the femoral artery and aorta (lgEC50 WT: −7.03 ± 0.6, ADK VEC KO: −7.05 ± 0.8) was similar in the two groups. Wild‐type mice progressively developed LV systolic and diastolic dysfunction when they underwent transverse aortic constriction surgery, whereas ADK VEC ‐KO mice displayed a lesser degree in decline of LV function. Conclusions: Our results indicate that ADK inhibition selectively enhances microvascular vasodilator function, whereby it improves LV perfusion and LV contractile function under metabolic and hemodynamic stress.